GREAT UZBEK WRITER ABDULLA AVLONIY’S VIEWPOINTS ON EDUCATION AND UPBRINGING - Xilola Mahmudjonova Avazbek qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This work mainly invastigates Abdulla Avloniy’s work and his ideas about education and upbringing. Another goal from this work is to consider the features of lifestyle and upbringing methods of prominent poet Abdulla Avloni and his great attention to education in one of his immortal works “Turkic Gulistan or Ethics”. Moreover, it concerns developing standards for what constitutes "education" and the significance of learning in the development of educational fields. Building educational fields over cultural domains is achievable thanks to knowledge of education, which transforms information into knowledge and knowledge into education. And to do this, one must build an educational relationship in which shared activity serves as the main working tool while competently carrying out teaching functions.